Preparation method of high-purity lithium sulfide
Preparation of high-purity lithium sulfide by three-time calcination method solves the problem of high preparation cost of lithium sulfide in the prior art, and achieves low-cost and high-purity lithium sulfide preparation, which is suitable for the industrialization of sulfide solid electrolytes.
Patent Information
- Application Number
- CN202411827796.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-05-02
AI Technical Summary
The existing lithium sulfide preparation method is costly, which limits the industrialization development of sulfide solid electrolytes.
Three-time calcination method is used to prepare high-purity lithium sulfide. The first calcination uses low-cost lithium carbonate. The second calcination does not require expensive metal lithium salts. The third calcination removes excess sulfur and reduces production costs.
It effectively reduces the production cost of lithium sulfide, improves its purity, is suitable for large-scale production, and improves the electrochemical performance of sulfide solid electrolytes.
Smart Images

Figure CN119911878A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery material preparation, and in particular to a method for preparing high-purity lithium sulfide. Background Art
[0002] With the rapid development of the electric vehicle industry, the market demand for lithium-ion batteries has further expanded. Traditional lithium-ion batteries have great safety risks due to their flammability and explosion. In addition, traditional lithium-ion batteries use liquid electrolytes, and the volatile organic compounds in the liquid electrolytes can cause short circuits and ruptures in the battery during the cycle.
[0003] All-solid-state lithium batteries use non-flammable solid electrolytes with good thermal stability and a wide electrochemical window, which can be better compatible with high-voltage cathode materials. In addition, because lithium metal anodes are used, they have higher specific surface area power and energy density, and are the preferred development direction for next-generation energy storage devices. Solid electrolytes replace traditional liquid electrolytes and separators in batteries. There are three types of solid electrolytes: polymers, oxides, and sulfides. Sulfide solid electrolytes are the best because the ionic conductivity of sulfide solid electrolytes (~10-2S / cm) is higher than that of polymer and oxide solid electrolytes at room temperature, which can reduce interfacial impedance and help improve the performance of batteries in high-speed charging and discharging states. However, one of the key issues hindering the application of sulfide solid electrolytes is the high price (so far, $100,000 to $200,000 per kilogram). The main reason for the high price of sulfide solid electrolytes is the high cost of its raw material lithium sulfide.
[0004] CN112607712A discloses a method for preparing lithium sulfide by solid phase synthesis, wherein lithium metal is used as a lithium source, sulfur powder is used as a sulfur source, lithium powder and sulfur powder are mixed in a certain proportion and placed in a ball mill, and then the two are reacted in the tank by solid phase ball milling to finally generate lithium sulfide. Although the method is simple to operate, the use of metallic lithium makes the cost extremely high and is not suitable for large-scale production. CN114188509A discloses a method for preparing a lithium sulfide electrode based on carbon nanotube encapsulation, and the specific method is as follows: first, a certain amount of metallic lithium and carbon nanotubes are heated in a tubular furnace, then a certain amount of elemental sulfur and metallic lithium / carbon nanotube mixed material are placed in a tubular furnace quartz tube and heated to obtain a crude lithium sulfide product, and finally the obtained material is immersed in ethanol for 1 hour and then centrifuged to obtain a carbon nanotube-encapsulated lithium sulfide electrode material. The method is complicated to operate, and the cost of the prepared lithium sulfide is too high. In addition, CN118289714A discloses a method for preparing high-purity lithium sulfide with an organic solvent, which is to mix lithium fluoride and chlorosilicon compound and dissolve them in a first organic solvent, then pass hydrogen sulfide gas, and heat the reaction to obtain lithium sulfide, fluorosilicon compound gas and hydrogen chloride gas, and then wash and filter with a second organic solvent, and finally obtain the lithium sulfide finished product after reduced pressure drying. Although this method obtains high-purity lithium sulfide, its synthesis cost is still high because the organic solvent therein is expensive. Therefore, developing a low-cost lithium sulfide preparation method is of great significance for realizing the industrialization development of sulfide solid electrolytes. Summary of the invention
[0005] In view of the above-mentioned prior art, the object of the present invention is to provide a method for preparing high-purity lithium sulfide, so as to achieve low-cost and high-purity preparation of lithium sulfide.
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] The present invention provides a method for preparing high-purity lithium sulfide, comprising the following steps:
[0008] (1) calcining a battery-grade lithium source precursor for the first time in an air atmosphere to obtain lithium oxide powder;
[0009] (2) mixing lithium oxide powder and sulfur powder, ball milling, tableting, and then transferring to an inert gas protection, sealing in a high-pressure reactor for a second calcination, and crushing to obtain a crude lithium sulfide product;
[0010] (3) The crude lithium sulfide is calcined for the third time under the protection of an inert gas to obtain high-purity lithium sulfide.
[0011] Preferably, in step (1), the battery-grade lithium source precursor is lithium carbonate.
[0012] Preferably, in step (1), the temperature of the first calcination is 800-1000° C., and the calcination time is 2-4 hours.
[0013] Preferably, in step (2), the mass ratio of the lithium oxide powder to the sulfur powder is 5:3.
[0014] Preferably, in step (2), the particle size of the ball mill is 5-10 μm, and the tableting pressure is 150-200 MPa.
[0015] Preferably, in step (2), the inert gas is nitrogen.
[0016] Preferably, in step (2), the temperature of the second calcination is 600-800° C., and the calcination time is 3-5 hours.
[0017] Preferably, in step (3), the temperature of the third calcination is 700-800° C., and the calcination time is 2-4 hours.
[0018] Beneficial effects of the present invention:
[0019] The present invention adopts a three-calcination method, and selects lithium carbonate with low cost, stable content and weak corrosiveness as the raw material for the first calcination operation. Based on the first calcination, the second calcination does not need to use expensive metal lithium salts to stably prepare crude lithium sulfide, further reducing the cost. The main function of the third calcination is to remove excess sulfur and obtain high-concentration lithium sulfide. The three-calcination method provided by the present invention effectively reduces the production cost of lithium sulfide, and the preparation process is simple, the purity of the produced lithium sulfide is high, the equipment requirements are low, and it is suitable for mass production. And the sulfide solid electrolyte prepared by using the lithium sulfide produced by the preparation method provided by the present invention as a raw material has excellent electrochemical properties. This low-cost, large-scale synthesis of battery-grade Li2S method has laid a solid foundation for the industrialization of sulfide solid electrolytes.
[0020] The method for preparing lithium sulfide in the prior art is carbon thermal reduction, specifically: using fully carbonized coconut shell carbon and dehydrated Li2SO4 as raw materials. First, Li2SO4 and coconut shell carbon are weighed at a molar ratio of 1:3 and ball milled at 300rmp for 1.5 hours, and then the mixture of Li2SO4 and coconut shell carbon is pressed in close contact and calcined for 5 hours under a flowing nitrogen atmosphere at 820°C to prepare a crude Li2S product. The crude Li2S product is quickly transferred to a glove box filled with argon, dissolved in ethanol, and filtered to remove insoluble impurities. The solvent ethanol is then evaporated to obtain Li2S. Finally, outside the glove box, the obtained Li2S is sintered at 700°C in a flowing nitrogen atmosphere for 3 hours to prepare high-purity Li2S. The cost of lithium sulfide synthesized by this preparation method is about 1,028,000 yuan / ton, and the purity is 99.8%. The cost of synthesizing lithium sulfide using the preparation method provided in this application is about 800,000 yuan / ton, and the purity can reach 99.9%, which significantly reduces the production cost of lithium sulfide. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is the XRD pattern of the high-purity lithium sulfide synthesized in Example 1 (wrapped with polyimide tape during testing).
[0022] Figure 2 This is the XRD pattern of the high-purity lithium sulfide synthesized in Comparative Example 1 (wrapped with polyimide tape during testing).
[0023] Figure 3 This is the XRD pattern of the high-purity lithium sulfide synthesized in Comparative Example 2 (wrapped with polyimide tape during testing).
[0024] Figure 4 The electrochemical performance test of the sulfide system all-solid-state battery prepared in Example 1 is as follows: Figure 4 A is the electrochemical charge-discharge curve diagram of the charge-discharge test voltage interval of Example 1; Figure 4 B is a full battery cycle performance diagram of the charge and discharge test voltage range of Example 1; Figure 4 C is the cycle performance diagram of the charge and discharge test voltage range of Example 1.
[0025] Figure 5 The electrochemical performance test of the sulfide system all-solid-state battery prepared in Comparative Example 1 is as follows: Figure 5 A is the electrochemical charge-discharge curve diagram of the charge-discharge test voltage range of Comparative Example 1; Figure 5 B is a full battery cycle performance diagram of the charge and discharge test voltage range of comparative example 1; Figure 5 C in the middle is the cycle performance diagram of the charge and discharge test voltage range of comparative example 1.
[0026] Figure 6The electrochemical performance test of the sulfide system all-solid-state battery prepared in Comparative Example 2 is as follows: Figure 6 A is the electrochemical charge-discharge curve diagram of the charge-discharge test voltage range of Comparative Example 2; Figure 6 B is a full battery cycle performance diagram of the sulfide system all-solid-state battery in the charge and discharge test voltage range prepared in Comparative Example 2; Figure 6 C in the middle is the cycle performance diagram of the charge and discharge test voltage range of comparative example 2. DETAILED DESCRIPTION
[0027] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0028] As mentioned in the background technology, all-solid electrolytes are safer and more stable than liquid electrolytes, and are better materials for preparing lithium-ion batteries. However, their high prices limit their application, mainly due to the high cost of preparing lithium sulfide raw materials required for preparing solid electrolytes. Therefore, low-cost large-scale synthesis of Li2S is the key to promoting the practical application of all-solid electrolytes.
[0029] Based on this, the present invention provides a high-purity lithium sulfide and a preparation method and application thereof. A high-purity lithium sulfide is prepared by a three-time calcination method, and the three-time calcination method specifically comprises the following steps:
[0030] (1) A battery-grade lithium source precursor is first calcined in an air atmosphere to obtain lithium oxide powder. The calcination temperature is 800-1000° C. and the calcination time is 2-4 hours; the lithium source precursor is lithium carbonate.
[0031] (2) mixing lithium oxide powder and sulfur powder, ball milling and tableting, the ball milling particle size is 5-10 μm, and then tableting the mixture at a tableting pressure of 150-200 MPa, and then transferring to an inert gas protection, sealing in a high-pressure reactor for a second calcination, the calcination temperature is 600-800° C., the calcination time is 3-5 h, and then crushing to obtain a crude lithium sulfide product.
[0032] (3) The crude lithium sulfide is calcined for the third time under the protection of an inert gas at a calcination temperature of 700-800° C. for a calcination time of 2-4 hours to obtain high-purity lithium sulfide.
[0033] In the above preparation method, the present invention firstly uses lithium carbonate to carry out a first calcination in an air atmosphere to obtain lithium oxide. The reaction occurring during the first calcination is: The chemical formula of the raw material lithium carbonate used is Li2CO3, which is composed of lithium and carbonate and is widely used in the field of battery manufacturing. Compared with another common lithium oxide material-lithium hydroxide, the lithium content in lithium carbonate fluctuates less and is less corrosive. From the perspective of cost, lithium carbonate is also lower. Therefore, the present invention chooses to use lithium carbonate with stable content and weak corrosiveness as the raw material for the first calcination operation. The reaction that occurs in the second calcination is A crude lithium sulfide product is obtained. In this step of the reaction, lithium oxide and sulfur powder are calcined at high temperature in a nitrogen atmosphere. Based on the first calcination, the second calcination does not need to use expensive metal lithium salts, and a crude lithium sulfide product can be stably prepared, thereby reducing costs. The main function of the third calcination is to remove excess sulfur and obtain a high-concentration lithium sulfide. The three-calcination method provided by the present invention effectively reduces the production cost of lithium sulfide, and the preparation process is simple, and the produced lithium sulfide has high purity.
[0034] The following detailed description is for illustrative purposes only and is intended to provide further explanation of the present application, rather than to limit the scope of the present invention.
[0035] Example 1: Preparation method of high-purity lithium sulfide
[0036] (1) Weigh battery-grade lithium carbonate powder and calcine it at 1000°C in an air atmosphere, with a heating rate of 5°C / min and a calcination time of 2 h. After the temperature drops naturally, take out the calcined product and quickly transfer it to a glove box filled with argon.
[0037] (2) The calcined product is mixed with a certain proportion of sulfur powder (the mass ratio of lithium oxide powder to sulfur powder is 5:3), and the mixture is placed in a ball mill for ball milling with a ball milling particle size of 9 μm. The mixture is then pressed into a tablet press at a pressure of 120 MPa.
[0038] (3) In a glove box with a nitrogen atmosphere, the pressed lithium oxide and sulfur powder mixture is placed in a sealed high-pressure reactor, and then calcined in a muffle furnace at 800°C, with the heating rate maintained at 5°C / min, and the calcination time is 3 hours. After the temperature drops naturally, the calcined product is taken out and crushed to 10 μm to obtain a crude lithium sulfide product.
[0039] (4) The crude lithium sulfide is placed in a corundum boat, wrapped with plastic wrap, and then transferred out of the glove box. It is placed in a tubular furnace and calcined at 800°C under nitrogen protection to remove excess sulfur. The heating rate is 5°C / min and the calcination time is 2h. After natural cooling, high-purity lithium sulfide is obtained.
[0040] Example 2: Preparation method of high-purity lithium sulfide
[0041] (1) Weigh battery-grade lithium carbonate powder and calcine it at 800°C in an air atmosphere, with a heating rate of 5°C / min and a calcination time of 4 h. After the temperature drops naturally, take out the calcined product and quickly transfer it to a glove box filled with argon.
[0042] (2) The calcined product is mixed with a certain proportion of sulfur powder (the mass ratio of lithium oxide powder to sulfur powder is 5:3), and the mixture is placed in a ball mill for ball milling with a ball milling particle size of 5 μm. The mixture is then pressed into a tablet press at a pressure of 150 MPa.
[0043] (3) In a glove box with a nitrogen atmosphere, the pressed lithium oxide and sulfur powder mixture is placed in a sealed high-pressure reactor, and then calcined in a muffle furnace at 600°C, with the heating rate maintained at 5°C / min, and the calcination time is 5h. After the temperature drops naturally, the calcined product is taken out and crushed to 10 μm to obtain a crude lithium sulfide product.
[0044] (4) The crude lithium sulfide is placed in a corundum boat, wrapped with plastic wrap, and then transferred out of the glove box. The boat is placed in a tubular furnace and calcined at 700°C under nitrogen protection to remove excess sulfur. The heating rate is 5°C / min and the calcination time is 4 hours. After natural cooling, high-purity lithium sulfide is obtained.
[0045] Comparative Example 1: Preparation method of lithium sulfide
[0046] Comparative Example 1 uses battery-grade lithium hydroxide powder as a preparation raw material, and other preparation methods are the same as those in Example 1, as follows:
[0047] (1) Weigh battery-grade lithium hydroxide powder and calcine it at 1000°C in an air atmosphere, with a heating rate of 5°C / min and a calcination time of 2 h. After the temperature drops naturally, take out the calcined product and quickly transfer it to a glove box filled with argon.
[0048] (2) The calcined product is mixed with a certain proportion of sulfur powder (the mass ratio of lithium oxide powder to sulfur powder is 5:3), and the mixture is placed in a ball mill for ball milling with a ball milling particle size of 9 μm. The mixture is then pressed into a tablet press at a pressure of 120 MPa.
[0049] (3) In a glove box with a nitrogen atmosphere, the pressed lithium oxide and sulfur powder mixture is placed in a sealed high-pressure reactor, and then calcined in a muffle furnace at 800°C, with the heating rate maintained at 5°C / min, and the calcination time is 3 hours. After the temperature drops naturally, the calcined product is taken out and crushed to 10 μm to obtain a crude lithium sulfide product.
[0050] (4) The crude lithium sulfide is placed in a corundum boat, wrapped with plastic wrap, and then transferred out of the glove box. It is placed in a tubular furnace and calcined at 800°C under nitrogen protection to remove excess sulfur. The heating rate is 5°C / min and the calcination time is 2h. After natural cooling, high-purity lithium sulfide is obtained.
[0051] Comparative Example 2: Preparation method of lithium sulfide
[0052] Compared with Example 1, the preparation method of Comparative Example 2 is different only in that the third calcination is not performed, as follows:
[0053] (1) Weigh battery-grade lithium carbonate powder and calcine it at 1000°C in an air atmosphere, with a heating rate of 5°C / min and a calcination time of 2 h. After the temperature drops naturally, take out the calcined product and quickly transfer it to a glove box filled with argon.
[0054] (2) The calcined product is mixed with a certain proportion of sulfur powder (the mass ratio of lithium oxide powder to sulfur powder is 5:3), and the mixture is placed in a ball mill for ball milling with a ball milling particle size of 9 μm. The mixture is then pressed into a tablet press at a pressure of 120 MPa.
[0055] (3) In a glove box with a nitrogen atmosphere, the pressed lithium oxide and sulfur powder mixture is placed in a sealed high-pressure reactor, and then calcined in a muffle furnace at 800°C, with the heating rate maintained at 5°C / min, and the calcination time is 3 hours. After the temperature drops naturally, the calcined product is taken out and crushed to 10 μm to obtain a crude lithium sulfide product.
[0056] Test Example 1: Lithium sulfide XRD detection and element determination
[0057] The lithium sulfide prepared in Example 1, Comparative Example 1 and Comparative Example 2 was measured using an X-ray machine. Figure 1-Figure 3 It can be seen that the preparation methods of Example 1, Comparative Example 1 and Comparative Example 2 all prepared lithium sulfide. Further, the elements in the lithium sulfide prepared in Example 1, Comparative Example 1 and Comparative Example 2 were determined using the ICP-OES method. The results showed that the lithium sulfide prepared by the three-step calcination method of Example 1 had higher contents of sulfur and lithium, indicating that the lithium sulfide prepared in Example 1 has higher purity.
[0058] Table 1: Elemental analysis of lithium sulfide prepared in Example 1
[0059]
[0060] Table 2: Elemental analysis of lithium sulfide prepared in Comparative Example 1
[0061]
[0062] Table 3: Elemental analysis of lithium sulfide prepared in Comparative Example 2
[0063]
[0064] Experimental Example 2: Conductivity detection of sulfide solid electrolytes prepared from different lithium sulfide raw materials
[0065] The lithium sulfide prepared in Example 1, Comparative Example 1 and Comparative Example 2 was used as a raw material, and a sulfide solid electrolyte was prepared respectively using a high temperature liquid phase method. The specific steps for preparing different sulfide solid electrolytes are as follows:
[0066] S1, under an argon atmosphere, lithium sulfide, phosphorus pentasulfide and sulfur powder are poured into a container in a mass ratio of 75:25:400, dispersed at a stirring speed of 800 r / min, and the materials are stirred evenly to prepare a mixed material;
[0067] S2, heating the mixed material stirred in step S1 to a melting temperature of 180° C., completely melting the sulfur powder in the mixed material, and maintaining the molten liquid phase state of the sulfur powder for 30 minutes to obtain a molten material;
[0068] S3, heating the molten material prepared in step S2 to a heating temperature of 240° C., maintaining the temperature for 2 hours, and then naturally cooling the molten material to room temperature to obtain a product;
[0069] S4, weighing 120 mg of the product prepared in step S3, and performing tableting at a pressure of 10 MPa to prepare a sulfide solid electrolyte with a structural formula of 75Li2S·25P2S5.
[0070] The sulfide solid electrolytes prepared using lithium sulfide as raw materials in Example 1, Comparative Example 1 and Comparative Example 2 were marked as Example 1 Group, Comparative Example 1 Group and Comparative Example 2 Group, respectively. The conductivity of the sulfide solid electrolyte prepared in each group was tested using a conventional AC impedance method. The test results are as follows:
[0071] Table 4: Conductivity test results
[0072] Grouping Conductivity (S / cm) Example 1 Group <![CDATA[1.03×10 -3 ]]> Comparative Example 1 <![CDATA[0.99×10 -3 ]]> Comparative Example 2 <![CDATA[0.42×10 -3 ]]>
[0073] The test results show that the sulfide solid electrolyte prepared using lithium sulfide prepared by the three-step calcination method of Example 1 as a raw material has better conductivity.
[0074] Experimental Example 3: Electrochemical performance test of all-solid-state batteries assembled from sulfide solid electrolytes prepared from different lithium sulfide raw materials
[0075] The sulfide solid electrolytes prepared in Example 1, Comparative Example 1 and Comparative Example 2 are used as electrolytes for all-solid-state batteries. The specific steps for assembling all-solid-state batteries of different sulfide systems are as follows:
[0076] S1, under argon atmosphere, the Li-In negative electrode was first pressed onto the negative electrode stainless steel column at a pressure of 360 MPa and covered with a polyoxymethylene sleeve;
[0077] S2, pouring 70 mg of electrolyte onto the negative electrode assembled in step S1, and then pressing it onto the negative electrode at a pressure of 180 MPa as an electrolyte layer;
[0078] S3, pour 40 mg of the composite positive electrode (NCM positive electrode: electrolyte = 7:3) onto the electrolyte assembled in step S2, then place the gasket, and maintain the pressure at 720 MPa for 20 seconds, press the composite positive electrode onto the electrolyte, and finally tighten the screws.
[0079] The sulfide system all-solid-state batteries prepared in Example 1, Comparative Example 1 and Comparative Example 2 were marked as Example 1, Comparative Example 1 and Comparative Example 2, respectively. The electrochemical performance of the sulfide system all-solid-state batteries prepared in each group was tested using the Wuhan Blue Electric Battery Testing System. The test results are as follows: Figure 4-6 : The results show that the sulfide system all-solid-state battery prepared using Example 1 has excellent electrochemical properties. The low-cost, large-scale method for synthesizing battery-grade Li2S provided by the present invention lays a solid foundation for the industrialization of sulfide solid electrolytes.
[0080] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing high-purity lithium sulfide, characterized in that: The following steps are involved: (1) calcining a battery-grade lithium source precursor for the first time in an air atmosphere to obtain lithium oxide powder; (2) mixing lithium oxide powder and sulfur powder, ball milling, tableting, and then transferring to an inert gas protection, sealing in a high-pressure reactor for a second calcination, and crushing to obtain a crude lithium sulfide product; (3) The crude lithium sulfide is calcined for the third time under the protection of an inert gas to obtain high-purity lithium sulfide.
2. The preparation method according to claim 1, characterized in that: In step (1), the battery-grade lithium source precursor is lithium carbonate.
3. The preparation method according to claim 1, characterized in that: In step (1), the temperature of the first calcination is 800-1000° C., and the calcination time is 2-4 hours.
4. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of the lithium oxide powder to the sulfur powder is 5:
3.
5. The preparation method according to claim 1, characterized in that: In step (2), the particle size of the ball mill is 5-10 μm, and the tableting pressure is 150-200 MPa.
6. The preparation method according to claim 1, characterized in that: In step (2), the inert gas is nitrogen.
7. The preparation method according to claim 1, characterized in that: In step (2), the temperature of the second calcination is 600-800° C., and the calcination time is 3-5 hours.
8. The preparation method according to claim 1, characterized in that: In step (3), the temperature of the third calcination is 700-800° C., and the calcination time is 2-4 hours.
Citation Information
Patent Citations
Method for preparing lithium sulfide from lithium metal
CN112607712A
Preparation method of lithium sulfide electrode based on carbon nanotube packaging means
CN114188509A
Cited By
Lithium sulfide, two-step metathesis preparation method and application of lithium sulfide in all-solid-state battery
CN121872329A